Integration of landscape spaces road: a multidimensional vision - Rodríguez Motril, Francisco José (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
This article gives an overview of the tour of research carried out by the author, to reflect the aspirations of freedom of movement and relational of the contemporary individual spaces on the most immediate to transport infrastructure, through the recognition and development of anthropological social potentialities that these offer us. That search is divided into two phases: a conceptual redesign, in which these spaces are displayed as a mechanism for personal fulfillment of the individual, which requires a particular treatment of space and time more of our own was hypertext. This treatment is evident as we shall see, in an anthropological dissection of the advertising campaigns for the products that we consume, which gives us a great emotional attachment with these spaces. Secondly, you can see the result of having identified as embodies these values through the analysis of a series of projects in which are reflected, in order to be able to remove a series of guidelines and common strategies that can be extrapolated to any other project. Once located, it is pointed out that its effectiveness requires establishing a series of determinations sponsored from the framework of the planning. The importance of all these aspects we see in the results of the R&D project for integration of acoustic screens developed in the motorway to the coast of Granada.
Keywords: Landscape design; hypertext; territory; technology; roads